Roles of Rufy3 in experimental subarachnoid hemorrhage-induced early brain injury via accelerating neuronal axon repair and synaptic plasticity - Yang Wang; Jianguo Xu; Wanchun You; Haitao Shen; Xiang Li; Zhengquan Yu; Haiying Li; Gang Chen (Molecular Brain)
Abstract RUN and FYVE domain-containing 3 (Rufy3) is a well-known adapter protein of a small GTPase protein family and is bound to the activated Ras family protein to maintain neuronal polarity. However, in experimental subarachnoid hemorrhage (SAH), the role of Rufy3 has not been investigated. Consequently, we aimed to investigate the potential role of Rufy3 in an in vivo model of SAH-induced early brain injury (EBI). In addition, we investigated the relevant brain-protective mechanisms. Oxyhemoglobin (OxyHb) stimulation of cultured primary neurons simulated vitro SAH condition. The SAH rat model was induced by infusing autologous blood into the optic chiasma pool and treating the rats with lentivirus-negative control 1 (LV-NC1), lentivirus-Rufy3 shRNA (LV-shRNA), lentivirus-negative control 2 (LV-NC2), lentivirus-Rufy3 (LV-Rufy3), or 8-pCPT-2′-O-Me-cAMP (8p-CPT) (Rap1 agonist). In experiment one, we found that the protein level of Rufy3 decreased and neuronal axon injury in the injured neurons but was rectified by LV-Rufy3 treatment. In experiment two, mRNA and protein levels of Rufy3 were downregulated in brain tissue and reached the lowest level at 24 h after SAH. In addition, the expression of Myelin Basic Protein was downregulated and that of anti-hypophosphorylated neurofilament H (N52) was upregulated after SAH. In experiments three and four, Rufy3 overexpression (LV-Rufy3) increased the interactions between Rufy3 and Rap1, the level of Rap1-GTP, and the ratio of Rap1-GTP/total GTP. In addition, LV-Rufy3 treatment inhibited axon injury and accelerated axon repair by activating the Rap1/Arap3/Rho/Fascin signaling pathway accompanied by upregulated protein expression levels of ARAP3, Rho, Fascin, and Facin. LV-Rufy3 also enhanced synaptic plasticity by activating the Rap1/MEK/ERK/synapsin I signaling pathway accompanied by upregulated protein expression levels of ERK1, p-ERK1, MEK1, p-MEK1, synaspin I, and p-synaspin I. Moreover, LV-Rufy3 also alleviated brain damage indicators, including cortical neuronal cell apoptosis and degeneration, brain edema, and cognitive impairment after SAH. However, the downregulation of Rufy3 had the opposite effect and aggravated EBI induced by SAH. Notably, the combined application of LV-Rufy3 and 8p-CPT showed a significant synergistic effect on the aforementioned parameters. Our findings suggest that enhanced Rufy3 expression may reduce EBI by inhibiting axon injury and promoting neuronal axon repair and synaptic plasticity after SAH.